Legal Politics Economic Democracy in Indonesia - Sujono, Imam; Nasution, Krisnadi (PT. Riset Press International, 2023)
This research aims to explain process of developing the Indonesian nation in this global era requires a strong economic system so that the general welfare of the people can be realized following the state objectives listed in the Fourth Paragraph of the Preamble of the 1945 Constitution. To realize these state objectives are further regulated in Article 33 of the 1945 Constitution (Post Amendment). Article 33 of the 1945 Constitution provides a foundation for building and developing the Indonesian economy. Apart from that, it can also be used as a filter by the government and the people of Indonesia in dealing with the negative impacts of the development of liberalization in the world economy in the 21st century. However, the Indonesian economic system which is based on Article 33 of the 1945 Constitution, at the level of implementation regulated by law, is not in line with the goals of the state and the interpretation of Article 33 of the Constitution itself, in the end, it is often not achieved in building and realizing an Indonesian economy that can realize people's welfare or people's prosperity. This is because the legal politics of the legislators wrongly designed the implementation of legal products in the Indonesian economic system which is based on a family economy called cooperatives which is difficult to materialize and is only for certain interests.